Summaries - Alle forfattere, Alle forfattere (Psyke & Logos, 2003)
<span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-latin; mso-fareast-language: EN-US; mso-ansi-language: DA; mso-bidi-language: AR-SA;">Summaries in english